2016
DOI: 10.4238/gmr.15017055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polymorphisms in codons 11, 72 and 248 of TP53 in Brazilian women with breast cancer

Abstract: ABSTRACT. The association between TP53 gene polymorphisms and breast cancer (BC) in Brazilian women is a controversial topic. In this cross-sectional study, we evaluated the association between clinical pathological variables and three polymorphisms (TP53*11, TP53*72, and TP53*248) in BC patients and controls. Genomic DNA was extracted from the blood cells of 393 participants; the cancer-free control subjects were 26-72 years old (41 ± 11.03) and the BC patients were 28-80 years old (51 ± 10.70). We used stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The heterozygous frequency ranges between 40 and 60% and the frequency of the homozygous genotype is ~10%. These frequencies are also similar to the frequencies in the healthy population [141,142,143,144]. Even though the prevalence of this mutation is variable across different populations, these results are similar to the average frequencies observed worldwide [146].…”
Section: Breast Cancer Candidate Gene Studies In Latin Americasupporting
confidence: 82%
See 1 more Smart Citation
“…The heterozygous frequency ranges between 40 and 60% and the frequency of the homozygous genotype is ~10%. These frequencies are also similar to the frequencies in the healthy population [141,142,143,144]. Even though the prevalence of this mutation is variable across different populations, these results are similar to the average frequencies observed worldwide [146].…”
Section: Breast Cancer Candidate Gene Studies In Latin Americasupporting
confidence: 82%
“…Similarly, a Mexican study reported a significant association between the c.1196A>G (rs25487) variant of the XRCC1 gene and breast cancer risk [121]. Variants in TP53 , which is an important gene in DNA-repair related pathways [140], were reported in Brazilian populations [83,84,85,114,141,142,143,144,145]. Four case-control studies assessed the rs1042522 (c.215C>A) variant, reporting negative results.…”
Section: Breast Cancer Candidate Gene Studies In Latin Americamentioning
confidence: 99%
“…Since the dysfunction of cell cycle can result in the development of cancer, genetic mutations in the p53 gene are suggested to alter host's susceptibility to thyroid cancer [25]. There are several common single nucleotide polymorphisms in the p53 gene, and P53 codon 11, 47, 72, and 248 polymorphisms are the three most studied ones [26]. p53 codon 72 polymorphism is a G to C substitution at exon 6, which further results in an amino acid change from Arg to Pro [27].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the inclusion criteria, 81 studies were selected for extensive analysis [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,…”
Section: Methodsmentioning
confidence: 99%